Current working panorama in the Physical Activity and Sport field - A. Sánchez; S. Rebollo (Asociación Española de Ciencias del Deporte, 2010)
The article aims it at identify and to defining the currents fields and activities which professionals of Physical Education and activities in which, professionals in Physical Education and Sport Activities which, in the margin of other circumstances, are chosen on the basis of vocational, labour and/or economical factors. They are decisive in four fields such as teaching, researching, sport management-recreation, sport training and physical activity for the health and each of these characteristics is defined within its own field. Likewise, an analysis is given of the different stydy plans, from the double perspective of academic training and existing legal norms, to be able to put forward a proposal about the assignments of the fields and functions of both of them. Inmediattely after, an analysis of the laboor relation situation, both in the situation of being employed by a third party or in the situation of self-employment, endinf with various conclusions and proposals aimed at rregulating the labour frame of these professionals. KEY WORDS: Professional fields, vocational factors, working relations, academic training, teaching-research, management, recreational activities, sport training activities, health-relateds physical activity .